PENGARUH USER-GENERATED CONTENT SEBAGAI ALAT KOMUNIKASI BISNIS TERHADAP KREDIBILITAS INFORMASI WEBSITE “TOKOPEDIA” - Muhammad Fariz Pinuji; Satiri Satiri (Inter Script : Journal of Creative Communication, 2019)
This study aims to determine the effect of User-Generated Content as a Business Communication Tool on the Credibility of 'Tokopedia' Website Information. This is considering, the factor of content creation by other users can influence consumers in making purchasing decisions. Therefore, product content or reviews that are objective, accurate, and relevant to the product posted by other users will make the information look credible to other parties. The theory used for independent variables is the E-WOM theory, and user-generated content is measured by four dimensions of reciprocity, responsiveness, non-verbal information, and response speed. Whereas, the theory for the dependent variable uses the model of adopting information, information credibility is measured by two dimensions namely the quality of the argument and the credibility of the source. The research findings show that user - generated content as a business communication tool has a significant effect on the credibility of the Tokopedia website information. This means that the content or comments made by other users on the Tokopedia website look credible so that other consumers who read them trust the information contained in the comments column. Great Influence of User - Generated Content as a Business Communication Tool Against the Credibility of Tokopedia Website Information, obtained by 0.624 including the category of strong influence. This means that the content or product reviews made by other users on the Tokopedia Website look credible information. The conclusion of the study shows that user - generated content as a business communication tool has a significant effect on the credibility of the Tokopedia website information, and the category of influence is included category strong.